Natal conditions, lifespan and lifetime reproductive success of European blackbirds. (17th August 2019) - Wysocki, Dariusz; Jankowiak, Łukasz; Cholewa, Marta; Zyskowski, Dawid
Abstract: Even though much has been published in recent years on the factors affecting the lifespan and lifetime reproductive success of birds, there are still gaps in our knowledge. Here, we present the results of a long-term study of European blackbirds which examined the effect of natal conditions on lifespan and lifetime reproductive success (expressed by the number of fledglings) of 152 nestlings (72 males and 80 females) ringed in the Stefan Żeromski Park in Szczecin (NW Poland). We have complete information regarding parental age, family brood (first-egg laying date, clutch size, and hatching sequence), bird size, lifetime reproductive success, pair density and weather conditions during the natal year. For males, total fledgling production was the smaller, the later the laying date of the family brood, but increased with mean daily precipitation and pair density in the natal year. In the case of females, we did not find any significant relationships between their lifetime reproductive success and the above parameters. Male lifespan increased with mean daily precipitation and bird density, but only pair density had a positive effect on female lifespan. We suggest that for females, genetic factors could be more important for their reproductive success than for males. In addition, a blackbird's lifespan depends strongly on environmental factors. Abstract : Lifetime reproductive success for male, but not female, European blackbirds depends on laying date and rainfall. Male lifespan increased with mean daily precipitation and bird density, but only pair density had a positive effect on female lifespan. We found no effect of age of either parent on the total fledgling production and lifespan of an individual bird, and neither did we find any effect of clutch size or hatching sequence in the family brood.